Driving h‐osteoblast adhesion and proliferation on titania: peptide hydrogels decorated with growth factors and adhesive conjugates‡. (1st June 2014) - Dettin, M.; Zamuner, A.; Iucci, G.; Messina, G. M. L.; Battocchio, C.; Picariello, G.; Gallina, G.; Marletta, G.; Castagliuolo, I.; Brun, P.; Morelli, Giancarlo; Toniolo, Claudio; et al.
<x xml:space="preserve">Abstract</x> Hydrogels from self‐assembling ionic complementary peptides have been receiving much interest from the scientific community as mimetics of the extracellular matrix that can offer three‐dimensional support for cell growth or become vehicles for the delivery of stem cells or drugs. These scaffolds have also been proposed as bone substitutes for small defects as they promote beneficial effects on human osteoblasts. In order to develop a novel bioactive titanium implant, we propose the introduction of a layer of ionic‐complementary self‐assembling peptides (EAbuK) on Ti whose surface has been previously sandblasted and acid etched. The peptide layer is anchored to the metal by covalent functionalization of titania with self‐assembling sequences. The peptide layer has also been enriched by the insulin‐like growth factor‐1 incorporated to the layer and/or a conjugate obtained by chemoselective ligation between EAbuK and a sequence of 25 residues containing four GRGDSP motifs per chain. X‐ray photoelectron spectroscopy studies confirmed a change in the surface composition in agreement with the proposed decorations. An evaluation of the contact angle showed a substantial change in wettability induced by the peptide layer. The human osteoblast adhesion and proliferation assays showed an increase in adhesion for the surfaces enriched with conjugate at a concentration of 3.8 × 10−7 m and an enhanced proliferation for samples enriched with insulin‐like growth factor‐1 at the highest concentration tested (2.1 × 10−5 m). Copyright © 2014 European Peptide Society and John Wiley & Sons, Ltd.